STUDI PENGARUH TEMPERATUR AUSTENITIASI DAN HOLDING TIME PADA PROSES HARDENING BAJA K 460 - Suyadi, Suyadi (METANA, 2006)
Abstract on the harcening process of K 460 steel, austenite temperature and holding time plays very important roles in influencing the result of hardening. In this research, austenite tenrperature variatiorrs are 755oc, 770 oc,785oc. 8l5oc, and 840oc with holding time of 5'30',60' and 120'. Then research result indicates that on 755oc. variation of the holding time produce high increase of hardness. For the others temperature need 30' to reach homogeny phase and more 30' holding time make the hardness relative constant. Meanwhile, the impact strength would be varied caused by intemal stress and residual austenite. For statistical analysis with 99oc accuracy, it's found that the effect-of temperature and holding time and it's both interactions make the number of hardness and the impact strength grow significantly. Â  Key words : hardening, temperature austenite, holding time